Konsep Pohon Keputusan - Zuhra Nahda; Aini Rahma; Lukman Hakim AlFath; Suhairi Suhairi (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Problem solving is an attempt to find a way out of a difficulty, to achieve a goal that is not immediately achievable. At the stage of planning a solution, a manager can identify problem-solving strategies. Work in solving or solving problems is much more complicated than just problem solving. However, it is safe to say that problem solving is one of the main activities that often determines the success or failure of career management. The results of this article are based on the analysis of researchers in general there are several things that need to be known from decision making, such as models, theories, processes, and others. Kata kunci: Decision making, such as models, theories,process, and so on.